KOMPARASI KINERJA DAN KETAHANAN KREDIT ANTARA PERBANKAN KONVENSIONAL DAN PERBANKAN SYARIAH - Frisky Elisa; Ida Busneti (Media Ekonomi, 2015)
This research aims to know the factors affecting the performance and credit resilience at cinvensional and Islamic banks. In addition to comparing the performance and credit resilience of the convensional and Islamic banks. Using Pooled methods.  This research uses the return on asset (ROA) for performance bankings are measure non-performing loan (NPL) / non-performing finance (NPF) to credit resilience. Factor that are used to looking at banking performance, among others, the lain net interest margin (NIM), non-performing loan (NPL) atau non-performing finance (NPF), Loan to deposit ratio (LDR), dan BOPO. While credit resilience, fators that are used among others inflation, exchange rate, Loan to deposit ratio (LDR) dan capital adequacy ratio (CAR). This research uses a conventional five banks and five Islamic banks from 2010 quarter 01 – 2013 quarter 02. The data used in this study were obtained from quarterly report of the bank for 2010-2013. Badan Pusat Statistik and Bank Indonesia. Result of analysis of this study that the performance of conventional banks is influential NPL and BOPO while in credit resilience is inflation, in a ratio impact on Islamic banking performance as BOPO and influencing credit resilience is CAR